ТАРИХИЙ-БАДИИЙ АСАРЛАР ВОСИТАСИДА КУРСАНТЛАРДА ҲАРБИЙ ЖАСОРАТ СИФАТЛАРИНИ РИВОЖЛАНТИРИШ ТАМОЙИЛЛАРИ - Муродиллаева, М.У. (SCIENCE and SOCIETY, 2021)
In this article, there is descibed the development of military courage qualities as one of the professional activities of future officers in higher military educational institutions, the effective use of the means of development of these qualities in the educational process are given in detail.
Keywords: higher military educational institutions; historical-artistic works; development of qualities of military courage; principles of development of qualities of military courage